Silvio Gesell és a helyi pénzek - Bánóczy, János (Acta Scientiarum Socialium, 2013)
Silvio Gesell and local currency Analyzing the economic views of Silvio Gesell, or the problem of local money, it is impossible not to deal with the question how economists are considering money. As a result of these investigations it will be seen that the mainstream schools of economics with a more than 250 years history have only touched the real connection between money and the economy, these directions of economic theory have never analyzed the outstanding relationship between money and society. The money they have introduced into their models is real money. It is paradox, even this classical approach occludes, or does not let appear the real function of money, neither in their descriptions, nor in their models. Therefore it is wise to ask at the beginning of the present investigation what economists do know really about that, what is called money. It is an essential point that the role of money can be understood only in its social context, taking into account the concrete social circumstances of the considered period, gold money played – because of its property to serve as wealth title – a very special role in the history of monetary processes. The absolute scarcity of gold has implied its substitution by a bill of exchange, which is – based on the discounting practice – a bond with an officially unknown interest rate; selling and buying these bonds is the individual decision of two economic actors. Taking some examples from the history of money we mention some types of money not perpetuating their value, but there are other types of money with stable value. After having investigated the problem of introducing private interest rates, the analysis will arrive to the problem of subprime crises as the main important problem in present times, as an additional effect of the process called globalization. As probably efficient strategy against the negative effects of the globalization, some representatives of alternative economics suggested the introduction of local money, closely connected to some ideas expressed by Gesell in his theory of money. In the next part of this paper three economists (George, Proudhon, Gesell), rele-vant for the present problem, will be introduced. After some historical examples of local money we turn to recently issued local moneys. Comparing the existing local moneys with Gesell’s theory, analyzing how these modern forms of local money fulfill Gesell’s requirements, the basis is given to provide an answer to the question what justifies the existence of local money. Finally some conclusions will be drawn relevant for theory as well as for practical business.